Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.32738/jeppm.201601.0003
|View full text |Cite
|
Sign up to set email alerts
|

 Entrepreneurial Orientation vs. Innovativeness of Small and Medium Size Enterprises

Abstract: This study aims to examine the role of entrepreneurial orientation (entrepreneurship orientation) in innovation level among Small and Medium Size Enterprises (SMEs). A questionnaire survey was conducted among 137 firms in the Podlaskie Region. Three hypotheses related to entrepreneurial orientation and innovativeness level were examined by Structural Equation Modeling (SEM). The relation between two constructs of entrepreneurial orientation and innovativeness, that is proactiveness and risk taking were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 36 publications
2
38
0
7
Order By: Relevance
“…In turn, all EO dimensions were found to significantly and positively affect TI, which is in line with the extant literature (e.g., Ergün et al, ; Dess & Lumpkin, ; Rauch et al, ; Vora et al, ; Ejdys, ; Yu et al, ). Essentially, EO refers to a behavior that is aimed at focusing on identifying, creating, seizing, and exploiting unique business opportunities, through capitalizing on enhanced knowledge and experience (Dess & Lumpkin, ; Simsek & Heavey, ).…”
Section: Discussionsupporting
confidence: 89%
“…In turn, all EO dimensions were found to significantly and positively affect TI, which is in line with the extant literature (e.g., Ergün et al, ; Dess & Lumpkin, ; Rauch et al, ; Vora et al, ; Ejdys, ; Yu et al, ). Essentially, EO refers to a behavior that is aimed at focusing on identifying, creating, seizing, and exploiting unique business opportunities, through capitalizing on enhanced knowledge and experience (Dess & Lumpkin, ; Simsek & Heavey, ).…”
Section: Discussionsupporting
confidence: 89%
“…Entrepreneurial orientation can be defined as a multidimensional construct used at organizational or entrepreneur's level, although there is ongoing academic debate about the precise nature of those dimensions. Miller (1983) stated that the three dimensions of innovativeness, proactiveness and risk taking are the key aspects of entrepreneurship orientation, and this view is shared by many researchers (Covin and Slevin, 1989;Kreiser et al, 2013;Ejdys, 2016;Fellnhofer et al, 2016). To these, Lumpkin and Dess (1996) added two further dimensions to the construct: autonomy and competitive aggressiveness (see also Dess and Lumpkin, 2005;Maura et al, 2015).…”
Section: Entrepreneurial Orientationmentioning
confidence: 99%
“…Bearing in mind that innovativeness tends to be incremental overtime, there is a need for further investigations for causal relationships that are longitudinal in nature so as to evaluate the impact of afore-mentioned factors on innovativeness. In a cross sectional study, Ejdys (2016) confirmed proactivity affected innovativeness in SMEs. This study however did not explore other factors that could have jointly or singularly affected innovativeness in SMEs in Poland.…”
Section: Discussionmentioning
confidence: 80%
“…In addition to this, other studies have shown that there are other variables beyond, entrepreneurial orientation that affect innovativeness of firms (Neely and Hii, 2012). Entrepreneurial orientation has been found to be a prerequisite for innovativeness (Hult et al, 2004;Renko et al, 2009;Perez-Luno et al, 2010;Laforet, 2011;Ruiz-Ortega et al, 2013;Ejdys, 2016). Innovativeness has been defined as "the firm's tendency or willingness to participate in support of new ideas, creativity and experimentation as well as to develop creative processes of technological and R&D leadership which result in new products, services or technological processes" (Ruiz-Ortega et al, 2013).…”
Section: Concept Of Entrepreneurial Orientationmentioning
confidence: 95%
See 1 more Smart Citation